Annual report on NMR spectroscopy. - Webb, Graham A. (Academic Press, 2016)
Annual Reports on NMR Spectroscopy provides a thorough and in-depth accounting of the progress made in nuclear magnetic resonance (NMR) spectroscopy and its many applications. Nuclear magnetic resonance (NMR) is an analytical tool used by chemists and physicists to study the structure and dynamics of molecules. In recent years, no other technique has gained as much significance as NMR spectroscopy. It is used in all branches of science in which precise structural determination is required, and in which the nature of interactions and reactions in solution is being studied. Annual Reports on NMR Spectroscopy has established itself as a premier resource for both specialists and non-specialists alike who want to become familiar with the new techniques and applications of NMR spectroscopy.